Seat Yourself : The Best of South Louisiana's Local Diners, Lunch Houses, and Roadside Stops - Cook, Alex V. (Book collections on Project MUSE., 2016)
"Louisiana can be a complicated place, but the state?s good food and friendly people are simple facts. Pairing these two indisputable truths, author Alex V. Cook takes readers to the many unsung diners, quirky low-fuss restaurants, and family-run establishments that serve up the very best of true Louisiana cuisine. From a gas station with the best boudin links to a Vietnamese bakery with mouthwatering b?nh m?, each of these lesser-known culinary gems stitched across southeast Louisiana offers tasty local fare in a down-to-earth atmosphere. Setting off from the state capital of Baton Rouge and winding through the back roads of Cajun country, then turning southward to the Gulf, and finally veering onto side streets in New Orleans, Cook profiles more than thirty must-visit eateries with wit and an eye for the authentic. Along the way, a culinary landscape emerges that is markedly genuine, surprisingly diverse, and deliciously free from affectation. With indispensable venue information, personal recommendations, and entertaining anecdotes, Seat Yourself: The Best of South Louisiana's Local Diners, Lunch Houses, and Roadside Stops is a vivid, humorous, and sharply written hat tip to those Louisiana?s constants: amazing food and great people" --from the publisher.